Design of Wind Turbine Vibration Monitoring System - Shoubin Wang; Wei Gong; Gang Su; Hongyue Sun (IAES Indonesian Section, 2013)
In order to ensure safety of wind turbine operation and to reduce the occurrence of faults as well as to improve the reliability of wind turbine operation, a vibration monitoring for wind turbine is developed. In this paper, it analyses the enlargement of all the parts of the structure and the working mechanism, the research method of wind turbine operation vibration is introduced, with the focus being the use of the sensor principle. Finally the hardware design and software of this system is introduced and the main function of this system is described, which realizes condition monitoring of the work state of wind turbines.